FUNGSI MUSIK SRAKALAN PADA ACARA RESEPSI PERNIKAHAN DI KABUPATEN BENGKAYANG - Apriani, Rina; Sanulita, Henny; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is the function of srakalan music at wedding reception event at Sungai Raya Village Sungai Raya District of Bengkayang Regency. The reason researchers choose art Srakalan in Sungai Raya Village because the function of srakalan music as a means of da'wah and entertainment. The method used is descriptive method with qualitative research form. The approach used is the ethnographic approach.The results of research are: (1) music function Srakalan is as a means of entertainment and religious. (2) Srakalan music in Sungai Raya Village originated from the 70s until now and still maintained its existence. (3) this research can be implemented to school on cultural arts subjects or in extracurricular activities in school. Given the function of music Srakalan play an important role in the wedding reception is expected art of music Srakalan no future generation.Keywords: use, music, srakalan, wedding reception.